2009
DOI: 10.1001/archoto.2009.159
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response During Therapy With Cisplatin or Radiation for Human Papillomavirus–Related Head and Neck Cancer

Abstract: The HPV-positive tumors are not more curable based on increased epithelial sensitivity to cisplatin or radiation therapy. Instead, radiation and cisplatin induce an immune response to this antigenic cancer. The implications of these results may lead to novel therapies that enhance tumor eradication for HPV-positive cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
211
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(231 citation statements)
references
References 28 publications
(49 reference statements)
9
211
0
5
Order By: Relevance
“…Increased MHC class I expression upon irradiation could in part explain why HPV-positive tumors with absent/low MHC class I expression still respond readily to therapy and are recognized by the immune system (91). Eliciting a vigorous immune response in this context, would be in line with data obtained in mice, where HPV-positive tumors were curable after cisplatin or radiation therapy only in immunocompetent and not in immunoincompetent mice (92). In that system, it was proposed that being able to mount an immune response was required to eradicate these tumors (92).…”
Section: Studies Focusing On Immunological and Stem Cell Markers In Tsupporting
confidence: 60%
See 1 more Smart Citation
“…Increased MHC class I expression upon irradiation could in part explain why HPV-positive tumors with absent/low MHC class I expression still respond readily to therapy and are recognized by the immune system (91). Eliciting a vigorous immune response in this context, would be in line with data obtained in mice, where HPV-positive tumors were curable after cisplatin or radiation therapy only in immunocompetent and not in immunoincompetent mice (92). In that system, it was proposed that being able to mount an immune response was required to eradicate these tumors (92).…”
Section: Studies Focusing On Immunological and Stem Cell Markers In Tsupporting
confidence: 60%
“…Eliciting a vigorous immune response in this context, would be in line with data obtained in mice, where HPV-positive tumors were curable after cisplatin or radiation therapy only in immunocompetent and not in immunoincompetent mice (92). In that system, it was proposed that being able to mount an immune response was required to eradicate these tumors (92).…”
Section: Studies Focusing On Immunological and Stem Cell Markers In Tsupporting
confidence: 59%
“…30 Cisplatinbased therapy results in tumor clearance in wild type but not in Rag 1 mice. 31 Two studies have shown that the proportion of T cells that are specific for HPV16 E7 peptides among CD8þ T cell is significantly increased (three to fourfold) in PBMC of patients with HPV-positive oropharyngeal cancer when compared with HPV-negative patients. 13,32 More recently, a flow cytometry analysis of peripheral blood samples of patients with OSCC before treatment showed that HPV-positive patients have an increased number of 33 found no significant difference in TIL infiltrates among HPVpositive and HPV-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Также есть данные, что опухолевым и иммунным взаи-модействием объясняется лучший ответ ВПЧ-пози-тивных опухолей. ВПЧ-позитивность ассоциирована с лимфоцитарным ответом, а на животных моделях показано, что иммунокомпетентность -это необхо-димое условие для полного лизиса опухоли [26,33].…”
Section: возможности таргетной терапии при мутациях онкогеновunclassified